E-010 Exploring differences in cortical volume in adults with pulsatile tinnitus: a cross-sectional study. (23rd July 2022) - Remer, J; Caton, M; Narsinh, K; Raj, A; Amans, M
Abstract : Introduction: Pulsatile tinnitus is a debilitating disease in which patient's hear a whooshing sound that correlates with heartbeat, leading to significantly impaired quality of life. 1 Many etiologies can result in pulsatile tinnitus including, idiopathic intracranial hypertension, dural arteriovenous fistulas and other intracranial vascular anomalies. 2 While prior studies have revealed cortical anatomical differences in patients with chronic tinnitus, 3 predominantly in locations such as the cingulate cortex, these studies are limited by small sample sizes, large age ranges, and excluded or at least failed to differentiate patients with pulsatile tinnitus. Purpose: To evaluate for differences in cortical and subcortical volume in patients with pulsatile tinnitus Materials/Methods: High-resolution T1 images were successfully obtained from 74 adults consisting of 37 participants with clinical diagnosis of either unilateral or bilateral pulsatile tinnitus recruited from our institution's pulsatile tinnitus clinic and 37 cognitively normal age matched controls from the local community. Subjects recruited were between the ages of 60 to 70 years old and data was acquired using MPRAGE or BRAVO acquisition protocols. Cortical thickness, cortical volume, and subcortical volume was calculated and analyzed using Freesurfer 4 for 34 brain regions in each hemisphere. Differences in these metrics for each neuroanatomical location were compared between groups using T-tests assuming unequal distributions and unequal variance. Significant anatomical difference was defined as p < 0.05 corrected for multiple comparisons using the Bonferroni corrections. Results: Participants in each group were matched for race, ethnicity, age, and confirmed to be neurocognitively intact without evidence of dementia or mild cognitive impairment. Tinnitus laterality was defined for each patient as well as concurrent idiopathic intracranial hypertension. Significant decreases in cortical volume was observed in the left rostral middle frontal gyrus and lateral orbitofrontal cortex. Discussion: While many studies explore differences in neuroanatomy in chronic tinnitus, very little data exists looking at structural anatomical differences in patients with pulsatile tinnitus. One prior study revealed that patients in a younger cohort from ages 24–53 had decreased cortical volume in the left orbitofrontal cortex as well as decreased volume in the bilateral putamen and right middle occipital gyrus. 5 Our results expand on these prior findings and reveal that patients ages 60–70 with pulsatile tinnitus exhibited statistically significant differences in their cortical anatomy. A larger study is needed to see if similar or different regions are affected in a wider patient age range. References: Liyanage SH, Singh A, Savundra P, et al. Pulsatile tinnitus . JLaryngol Otol 2006;120:93–97 CrossRef Medline Zhao, Pengfei, et al . Why does unilateral pulsatile tinnitus occur in patients with idiopathic intracranial hypertension?. Neuroradiology 2021; 63.2: 209–216 Elgoyhen, Ana Belén, et al . Tinnitus: perspectives from human neuroimaging. Nature Reviews Neuroscience 2015; 16.10: 632–642. Fischl, Bruce. FreeSurfer. Neuroimage 2012; 62.2: 774–781. Liu, Yawen, et al . Neuroanatomical alterations in patients with early stage of unilateral pulsatile tinnitus: a voxel-based morphometry study. Neural Plasticity 2018 (2018). Disclosures: J. Remer: None. M. Caton: None. K. Narsinh: None. A. Raj: None. M. Amans: None.